A review of the bulk layer pollutant transfer over Nigeria during the harmattan season (2007)
A review of the results of the bulk characteristics of the harmattan dust is presented to facilitate ease of reference and regional comparison where similar local effects exist. The meteorological interconnections are dealt with. The transport properties are presented, and are found to agree with the plume model for cascaded continuous sources on a 1km x 1km gnd point system. The wind profile is found to be consistent with turbulent electrode model of Willet.